1974
DOI: 10.1002/bjs.1800611017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of truncal and selective vagotomy on the release of pancreatic glucagon, insulin and enteroglucagon

Abstract: SUMMARYTo study the effect of vagotomy on the endocrine function of the pancreas, plasma pancreatic glucagon levels were studied during insulin-induced hypoglycaemia, and VAGOTOMY in one of its various forms is the most widely practised surgical treatment for chronic duodenal ulcer, but there remains controversy as to which variant is preferable. The theoretical argument in favour of selective vagotomy is that it preserves the vagal innervation of the pancreas and liver, but there is surprisingly little info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Lefebvre and colleagues [69] observed no glucagon release from the stomach during electrical vagal stimulation. Russell and colleagues [61] found no difference in plasma enteroglucagon levels when comparing patients with TV and SGV plus P.…”
Section: Enteroglucagonmentioning
confidence: 95%
See 3 more Smart Citations
“…Lefebvre and colleagues [69] observed no glucagon release from the stomach during electrical vagal stimulation. Russell and colleagues [61] found no difference in plasma enteroglucagon levels when comparing patients with TV and SGV plus P.…”
Section: Enteroglucagonmentioning
confidence: 95%
“…In studies using the isolated, perfused rat pancreas, acetylcholine induced a prompt release of insulin [57], and direct vagal stimulation resulted in a release of insulin [58,59]. Several studies [60][61][62][63] have demonstrated that after SPV or SGV plus P, basal serum insulin levels and the postprandial insulin output were not changed. After TV, the insulin response to an oral glucose tolerance test or a test meal was either diminished [60,62] or unchanged [61,63,64].…”
Section: Insulinmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a glucagon response to arginine in the patients tested in Group B is evidence of the presence of functional A cells, despite the low glucagon response during insulin infusion. Glucagon release during minor hypoglycaemia is under vagal control from a central glucoreceptor [10,11] rather than under direct control by circulating glucose levels. Our previous hypothesis that the impaired glucagon response was due to a selective form of autonomic neuropathy [3] cannot, however, explain the impaired responses in cortisol and growth hormone.…”
Section: Resultsmentioning
confidence: 99%